The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1242/jeb.222471
|View full text |Cite
|
Sign up to set email alerts
|

Wind and obstacle motion affect honeybee flight strategies in cluttered environments

Abstract: Bees often forage in habitats with cluttered vegetation and unpredictable winds. Navigating obstacles in wind presents a challenge that may be exacerbated by wind-induced motions of vegetation. Although wind-blown vegetation is common in natural habitats, we know little about how the strategies of bees for flying through clutter are affected by obstacle motion and wind. We filmed honeybees Apis mellifera flying through obstacles in a flight tunnel with still air, headwinds or tailwinds. We tested how their gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Wind direction was constant: bees flying in one direction experienced headwinds and in the other direction tailwinds. Up to 12 flights through the obstacles were elicited per bee, using full spectrum lights at each end of the tunnel [10,24]. Obstacle motion (stationary versus moving) was fixed for a given bee, but all bees experienced wind and still air, with wind condition switched after approximately six flights and the order of wind conditions alternated between bees.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wind direction was constant: bees flying in one direction experienced headwinds and in the other direction tailwinds. Up to 12 flights through the obstacles were elicited per bee, using full spectrum lights at each end of the tunnel [10,24]. Obstacle motion (stationary versus moving) was fixed for a given bee, but all bees experienced wind and still air, with wind condition switched after approximately six flights and the order of wind conditions alternated between bees.…”
Section: Methodsmentioning
confidence: 99%
“…In each case, animals navigate around a series of vegetative structures that functionally serve as obstacles and constrain navigable paths [5,6]. Traversing obstacles while in flight requires coordinated detection of obstacles (e.g., visually) and rapid alteration of the flight path, for example by decelerating, accelerating, or changing body orientation [7][8][9][10][11]. However, most studies of obstacle traversal in flight focus on behaviors required to completely avoid obstacles, with little consideration of what happens when animals do make contact with obstacles (e.g., collisions).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other experiments showed that the majority of domestic dogs tended to replicate their previous successful learning trips, but it was more challenging for the more experienced dog to adapt to a novel path again in their subsequent trips ( Pongrácz et al, 2001 , 2003 ). A few recent studies have analysed insects such as bumblebees and honeybees in minimally cluttered environments ( Baird and Dacke, 2016 ; Ong et al, 2017 ; Ravi et al, 2019 ; Burnett et al, 2020 ). These studies indicated that when individuals were confronted with obstacles with various spacing, insects chose the larger gap ( Ong et al, 2017 ; Ravi et al, 2019 ) and used a brightness-based strategy for choosing among the different gaps ( Baird and Dacke, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Visual detection of a predator depends on the spectral sensitivity of the prey’s eye (the ability of the eye to respond to specific wavelengths of the light spectrum; Cronin et al, (2014)), spatial acuity (the capacity to discriminate shape and pattern details; Caves et al, (2018)) and temporal resolution (time taken to process visual information; Cronin et al, (2014)). Furthermore, abiotic factors such as wind or obstacles can add to the visual clutter in a habitat (Burnett et al, 2020; Hennessy et al, 2020) and consequently hinder predator detection.…”
Section: Introductionmentioning
confidence: 99%